Investigation Of In-Vitro Anti-Oxidant & Anti-Ulcer Activity Of Polyherbal Medicinal Plants - Tyagi, Riya; Kumar, Roshan; Mishra, Ashish Kumar (Journal of Neonatal Surgery, 2025)
Peptic ulcer disease (PUD) remains a significant global health burden, characterized by recurrent gastric lesions and complications. Although proton pump inhibitors (PPIs) like esomeprazole are the standard treatment, their adverse effects and high cost drive the search for safer, cost-effective alternatives. This study investigated the gastroprotective effects of Rhodomyrtus tomentosa and Cynodon dactylon leaf extracts in a cold-water immersion-induced ulcer model in rats, which replicates cold stress–mediated mucosal damage through increased permeability and vasoactive mediator release. The antioxidant and cytoprotective properties of these botanicals were evaluated by comparing their efficacy with esomeprazole in reducing gastric lesions and oxidative stress. Results demonstrated that both plant extracts significantly attenuated ulcer severity, with the 400 mg/kg dose showing near-comparable efficacy to esomeprazole (ulcer length: 3.60 ± 0.25 mm vs. 2.60 ± 0.85 mm). Histopathological analysis revealed dose-dependent mucosal protection, with the high-dose extract group exhibiting only mild lesions, in contrast to severe hemorrhagic necrosis in controls. Furthermore, the extracts normalized gastric pH (7.50 ± 0.36 vs. control 5.70 ± 0.82) and reduced gastric juice volume (2.00 ± 0.65 cm³ vs. control 4.67 ± 0.54 cm³), suggesting acid suppression and cytoprotective mechanisms